Initiated Chemical Vapor Deposition of Crosslinked Organic Coatings for Controlling Gentamicin Delivery - Gianfranco Decandia; Fabio Palumbo; Annalisa Treglia; Vincenza Armenise; Pietro Favia; Federico Baruzzi; Katrin Unger; Alberto Perrotta; Anna Maria Coclite (MDPI AG, 2020)
A coating consisting of a copolymer of methacrylic acid and ethylene glycol dimethacrylate was deposited over a gentamicin film by initiated chemical vapor deposition with the aim of controlling the drug release. Gentamicin release in water was monitored by means of conductance measurements and of UV-vis Fluorescence Spectroscopy. The influence of the polymer chemical composition, specifically of its crosslinking density, has been investigated as a tool to control the swelling behavior of the initiated chemical vapor deposition (iCVD) coating in water, and therefore its ability to release the drug. Agar diffusion test and microbroth dilution assays against Staphylococcus aureus and Pseudomonas aeruginosa on cellulose coated substrates confirmed that the antibacterial activity of the drug released by the coating was retained, though the release of gentamicin was not complete.